Disability alliances and allies : opportunities and challenges - Carey, Allison C.; Ostrove, Joan M.; Fannon, Tara (Emerald Publishing Limited, 2020)
In Disability Alliances and Allies: Opportunities and Challenges, Allison Carey, Joan Ostrove and Tara Fannon have gathered an interdisciplinary team of leading experts, to offer nuanced analyses of the meaning and practice of being an ally and of building effective alliances that account for the structural, individual, and interpersonal challenges involved in amplifying disabled voices and centering the disability lived experience. The first section of this volume addresses cooperation and conflict in advocacy and activism across social movements, organizations, and institutions. It examines the formation of new alliances, what happens when interests collide, and the social and economic challenges of forming coherent unions. The second section engages issues of agency, autonomy, and identity in interpersonal relationships, highlighting the role of power and status, focusing on alliance dynamics between disabled and non-disabled people. For its breadth and depth of research, this volume of Research in Social Science and Disability is essential reading for researchers and students across the social sciences interested in disability, social movements, activism, and identity.
Prelims Introduction: Exploring the Opportunities and Challenges of Alliances and Allyship in the Lives of People with Disabilities Part I Structures and Systems That Shape Alliances Chapter 1 International Rights and Local Realities: Transnational Allies of the Disability Rights Movement in China Chapter 2 Allies, Enemies, or Indifferent? The Disability and Older Persons' Movements under Neoliberalism in Jamaica Chapter 3 Impasses of Disability Alliance Building in Bulgaria: Successful Phantom Activism and Toxic Grassroots Mobilization Chapter 4 "I've Used My Wide Array of Skills to Create a Life for Myself": Managing Narratives with Competing Goals in an Arts-based Disability Ally Organization Chapter 5 Allyship Changes in American Disability Protests over Five Decades: An Empirical Analysis Part II Relational Dynamics of Alliance Building Chapter 6 Nothing about "Us" without Whom? (Re)Cognizing Alliance between Disabled People and Care Workers in Direct-funded Attendant Services Chapter 7 Autistic Adult and Non-Autistic Parent Advocates: Bridging the Divide Chapter 8 Becoming Allies: The Transmogrification of the Role of American Sign Language/English Interpreters during the Deaf President Now Protest Chapter 9 Can We Broaden the Neurodiversity Movement without Weakening It? Participatory Approaches as a Framework for Cross-disability Alliance Building Chapter 10 A Different Story: Narrative Allyship across Ability.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: People with disabilities -- Social conditions; Social Science, People with Disabilities; Disability: social aspects